An analysis on Sino Russian cooperation in the Arctic in the BRI era - Alexeeva, Olga; Lasserre, Frederic (Polar Research Institute of China - PRIC, 2018)
Over the past decade Sino-Russian cooperation in the Arctic has emerged as one of the major topics of the Russia-China negotiations on how to expand their comprehensive strategic partnership and to bring it to a new level. China considers the Arctic region important for its economic interests and desires to be included in the development of the region and its economic potential. For Russia, the Arctic is a future strategic resource base that would replace the old depleting fields and assure Russia’s status as a major worldwide energy supplier. Despite many joint statements on deepening of the Sino-Russian cooperation in the development of the Arctic energy resources, the concrete results of these ambitious plans are few. Some joint projects were dropped, as China and Russia could not agree on the conditions of the deal, others are progressing very slowly and have an uncertain future. In 2017, China has expanded its “Belt and Road Initiative” (BRI) to the Arctic thus elevating the Sino-Russian cooperation in the Artcic to a higher level. How did the relationship between Russia and China evolve in the Arctic and how do Russia and China view and respond to the new Arctic dimension of the BRI? What factors limit the strategic rapprochement between China and Russia in the Arctic?